Agreement of Colposcope and Gynocular in Assessment of Cervical Lesions by Swede Score A Randomized, Crossover Pilot Trial - Ngonzi, Joseph; Bajunirwe, Francis; Wistrand, Charlotte; Mayanja, Ronald; Altman, Daniel; Thorsell, Malin; Wikstro¨m Shemer, Elisabeth Andrea (Journal of Lower Genital Tract Disease, 2013)
This study aimed to determine if criterion standard colposcopy could be provided by a pocket-sized battery-driven colposcope, the Gynocular.
Keywords: cervical cancer , colposcopy , cervical lesions , cytology , biopsy , Swede score , Gynocular